IRCI‐free multiple subband MIMO SAR. Issue 7 (16th April 2021) - AlShaya, Mohammed; Yaghoobi, Mehrdad; Mulgrew, Bernard
Abstract: An inter‐range cell interference (IRCI)‐free multiple subband multiple‐input multiple‐output (MIMO) synthetic aperture radar (SAR) algorithm is proposed to obtain a high‐resolution wide swath (HRWS) imaging. The received signals of the proposed configuration are formulated as multiple‐input single‐output (MISO) system identification problems using the principle of the displaced phase centre in a way that all the subband waveforms are processed simultaneously without the need to separate them at the receiver. This would maximise the bandwidth utilisation efficiency. The channel impulse response in the range dimension is identified using a frequency domain system identification‐‐based estimation algorithm, which is free from IRCI, instead of using conventional matched filters. A pulse repetition frequency lower than the Doppler bandwidth is used to obtain the HRWS imaging, and the resulted azimuth ambiguity is removed using a set of spatial filters applied on the received signals formulated as separate MISO system identification problems. Finally, both simulated and constructed raw data are used to validate the efficiency of the proposed algorithm.